Impact of microwave processing on phytochemicals, antioxidant status, anti-nutritional factors and metabolite profile of maize flour - Alla Yaswanth Naveen Kumar; Alonkrita Chowdhury; Rajesh Kumar; Vivek Kumar Maurya; Subhasis Batabyal; Mayukh Ghosh (Applied Food Research)
Microwave processing can enhance phytochemicals and antioxidants, and reduce anti-nutritional factors (ANFs) in food grains but optimizing processing parameters and investigating effects on overall metabolite profile are needed to ensure desirable nutritional outcomes. This study investigates the effects of microwaving maize flour at different wattage (300, 600, and 800 watt) and duration (1.5–9 min) combinations on its phytochemicals, antioxidant capacity, ANFs, and metabolomics profile, using nine treatment groups (T1-T9) and non-microwaved control samples.. Phytochemicals exhibited treatment-dependent changes. Total phenolics (947.95–1304.77 µg GAE/g) and flavonoids (482.73–916.82 µg QE/g) varied, with flavonol content increasing (6.59–43.35 µg CE/g) and soluble sugar content decreasing (6563.13–15,578.75 µg DE/g) compared to the control. Antioxidant activities, such as ABTS scavenging (360.45–638.92 µg GAE/g), total antioxidant capacity (1888.38–2250.54 µg AAE/g), and cupric-reducing capacity (1008.64–2004.09 µg AAE/g), showed treatment-specific variations. DPPH scavenging (559.64–981.07 µg AAE/g) and ferric-reducing ability (790.18–1175.89 µg AAE/g) increased, whereas ascorbic acid content decreased (742.5–1423.75 µg/g). For ANFs, condensed tannin content showed overall decrease (338.17–626.58 µg CE/g), while oxalate (0.29–0.47 mg/g) and phytate content (32,078.33–36,270 µg PAE/g) showed treatment-specific reduction. LCHRMS analysis revealed significant metabolite variations among treatment groups, forming distinct clusters in PCA, sPLS-DA, and dendrogram analyzes, comprising a diverse range of primary and secondary metabolites. The 600-watt, 2-minute microwave treatment was identified as optimal, boosting phytochemicals and antioxidants in maize flour while minimally impacting the main metabolite profile. The outcomes of this comprehensive analysis espouse microwave technology in maize-based food processing to benefit humans as well as the animal and poultry feed industries.